Is there specific set of steps to be followed when solving similar questions?
A number gives remainder 3 when divided by 4. Hence it is of the form 4m+3 where m = 0,1,2…
Now, 4m+3 gives remainder 4 when divided by 5. It means (4m+3)-4 is divisible by 5.
Hence, 4m-1=5n where n is some positive integer. n=(4m-1)/5.
But, 4m+3 gives remainder 5 when divided by 6. It means (4m+3)-5 is divisible by 6.
Hence, 4m-2=6f where f is some positive integer. f=(4m-2)/6.
Again, 4m+3 gives remainder 6 when divided by 7. It means (4m+3)-6 is divisible by 7.
Hence, 4m-3=7l where l is some positive integer. l=(4m-3)/7.
My confusion: What do I do now? Or am I even in the right path?
Please don't solve it using modular arithmetic. I don't know it yet.